2017
DOI: 10.1007/s00401-016-1665-7
|View full text |Cite
|
Sign up to set email alerts
|

Incipient progressive supranuclear palsy is more common than expected and may comprise clinicopathological subtypes: a forensic autopsy series

Abstract: We investigated 998 serial Japanese forensic autopsy cases (0-101 years old, mean age 61.7 ± 21.9), with no case selection, using immunohistochemistry to detect cases with progressive supranuclear palsy (PSP). Twenty-nine cases (mean age 82.3 ± 7.2 years, 11 males, 18 females) fulfilled the National Institute of Neuronal Disorders and Stroke (NINDS)-PSP pathological criteria (2.9% of all cases, 4.6% of cases over 60). All had neuronal and glial inclusions in the basal ganglia and brainstem. However, 13 cases h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 73 publications
3
53
0
Order By: Relevance
“…However, a study in Japan that included other PSP phenotypes in addition to PSP-RS found a total prevalence of 18 per 100,000 across all ages. 5 This higher prevalence number is consistent with estimates from autopsy series, 6 and suggests that the prevalence of the full spectrum of PSP syndromes is substantially higher than estimates based on PSP-RS alone. A cluster of PSP cases in an industrial city in France and a multicenter case-control study suggest that environmental risk factors influence PSP incidence.…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…However, a study in Japan that included other PSP phenotypes in addition to PSP-RS found a total prevalence of 18 per 100,000 across all ages. 5 This higher prevalence number is consistent with estimates from autopsy series, 6 and suggests that the prevalence of the full spectrum of PSP syndromes is substantially higher than estimates based on PSP-RS alone. A cluster of PSP cases in an industrial city in France and a multicenter case-control study suggest that environmental risk factors influence PSP incidence.…”
Section: Introductionsupporting
confidence: 67%
“…24 Two similar studies found PSP pathology in 4.6% of normal elderly subjects in a healthy aging cohort 12 and 4.6% of individuals over 60 in a large forensic autopsy series in Japan. 6 These numbers are in striking contrast to the low prevalence of PSP-RS, 4 suggesting that if accurate, most individuals with presymptomatic PSP do not develop overt disease.…”
Section: Presymptomatic Pspmentioning
confidence: 97%
See 2 more Smart Citations
“…The proposed early brain network affected by tau pathology may shed light on the use of in vivo tau imaging as a biomarker to identify preclinical or early CBD. Neuropathological series of clinical asymptomatic cases with early PSP pathology has also emerged in the literature [25], which contributes to improve our understanding of the early disease process of 4R-tauopathies.…”
Section: Mechanistic and Clinical Implications Of Preclinical Case Studymentioning
confidence: 99%